A new class of N-doped ionic PAHs via intramolecular [4+2]-cycloaddition between arylpyridines and alkynes - Mule, Ravindra D.; Shaikh, Aslam C.; Gade, Amol B.; Patil, Nitin T. (Chemical Communications, 2018)
Reported herein, for the first time, is a copper-promoted intramolecular [4+2]-cycloaddition cascade to access ionic N-doped polycyclic aromatic hydrocarbons (PAHs) with tunable emission wavelengths. It is shown that the reaction can be made catalytic with respect to Cu(OTf)(2) when an external oxidant, Selectfluor, was used.

External oxidant-dependent reactivity switch in copper-mediated intramolecular carboamination of alkynes: access to a different class of fluorescent ionic nitrogen-doped polycyclic aromatic hydrocarbons - Shaikh, Aslam C.; Banerjee, Somsuvra; Mule, Ravindra D.; Bera, Saibal; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
An interesting case of external oxidant-controlled reactivity switch leading to a divergent set of ionic nitrogen-doped polycyclic aromatic hydrocarbons (N-doped PAHs), is presented here, which is quite unrecognized in copper-mediated reactions. In the current scenario, from the same pyridino-alkyne substrates, the use of the external oxidant Ph1(0Ac)2, in combination with Cu(OTf)(2), gave N-doped spiro-PAHs via a dearomative 1,2-carboamination process; whereas, without the use of oxidant, an alkyne/azadiene [4 + 2]-cycloaddition cascade occurred to exclusively afford ionic N-doped PAHs. These newly synthesized N-doped PAHs further exhibit tunable emissions, as well as excellent quantum efficiencies.

Ionic pyridinium-oxazole dyads: design, synthesis, and application in mitochondrial imaging - Shaikh, Aslam C.; Varma, Mokshada E.; Mule, Ravindra D.; Banerjee, Somsuvra; Kulkarni, Prasad P.; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
We recently developed an oxidative intramolecular 1,2-amino-oxygenation reaction, combining gold(I)/gold(III) catalysis, for accessing structurally unique ionic pyridinium-oxazole dyads (PODs) with tunable emission wavelengths. On further investigation, these fluorophores turned out to be potential biomarkers; in particular, the one containing -NMe2 functionality (NMe2-POD) was highly selective for mitochondrial imaging. Of note, because of mitochondria's involvement in early-stage apoptosis and degenerative conditions, tracking the dynamics of mitochondrial morphology with such imaging technology has attracted much interest. Along this line, we wanted to build a library of such PODs which are potential mitochondria trackers. However, Au/Selecfluor, our first-generation catalyst system, suffers from undesired fluorination of electronically rich PODs resulting in an inseparable mixture (1:1) of the PODs and their fluorinated derivatives. In our attempt to search for a better alternative to circumvent this issue, we developed a second-generation approach for the synthesis of PODs by employing Cu(II)/PhI(OAC)(2)-mediated oxidative 1,2-amino-oxygenation of alkynes. Thes newly synthesized PODs exhibit tunable emissions as well as excellent quantum efficiency up to 0.96. Further, this powerful process gives rapid access to a library of NMe2-PODs which are potential mitochondrial imaging agents. Out of the library, the randomly chosen POD-3g was studied for cell-imaging experiments which showed high mitochondrial specificity, superior photostability, and appreciable tolerance to microenvironment changes with respect to commercially available MitoTracker green.

Gold-catalyzed alkynylative meyer-schuster rearrangement - Banerjee, Somsuvra; Ambegave, Shivhar B.; Mule, Ravindra D.; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2020)
By applying the ``interplay'' mode, which consolidates two key reactivity modes of gold catalysis, namely pi-activation mode and cross-coupling mode, the first alkynylative Meyer-Schuster rearrangement is designed and successfully implemented. The current protocol gives straightforward access to enynones, a highly valuable building block, from easily available propargyl alcohol feedstocks. Control experiments suggest an Au(III) catalyst triggers the Meyer-Schuster rearrangement, whereas monitoring the reaction with ESI-HRMS provided strong evidence in favor of a key alkynylgold(III) intermediate which supports the proposed ``interplay'' scenario.

High-throughput metabolomic and transcriptomic analyses vet the potential route of cerpegin biosynthesis in two varieties of Ceropegia bulbosa Roxb. - Gharat, Sachin A.; Shinde, Balkrishna A.; Mule, Ravindra D.; Punekar, Sachin A.; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Ramaswamy, Gopalakrishna; Giri, Ashok P. (Planta, 2020)
Ceropegia bulbosa is an important medicinal plant, used in the treatment of various ailments including diarrhea, dysentery, and syphilis. This is primarily attributed to the presence of pharmaceutically active secondary metabolites, especially cerpegin. As this plant belongs to an endemic threatened category, genomic resources are not available hampering exploration on the molecular basis of cerpegin accumulation till now. Therefore, we undertook high-throughput metabolomic and transcriptomic analyses using different tissues from two varieties namely, C. bulbosa var. bulbosa and C. bulbosa var. lushii. Metabolomic analysis revealed spatial and differential accumulation of various metabolites. We chemically synthesized and characterized the cerpegin and its derivatives by liquid chromatography tandem-mass spectrometry (LC-MS/MS). Importantly, these comparisons suggested the presence of cerpegin and 5-allyl cerpegin in all C. bulbosa tissues. Further, de novo transcriptome analysis indicated the presence of significant transcripts for secondary metabolic pathways through the Kyoto encyclopedia of genes and genomes database. Tissue-specific profiling of transcripts and metabolites showed a significant correlation, suggesting the intricate mechanism of cerpegin biosynthesis. The expression of potential candidate genes from the proposed cerpegin biosynthetic pathway was further validated by qRT-PCR and NanoString nCounter. Overall, our findings propose a potential route of cerpegin biosynthesis. Identified transcripts and metabolites have built a foundation as new molecular resources that could facilitate future research on biosynthesis, regulation, and engineering of cerpegin or other important metabolites in such non-model plants.
Keywords: 5-Allyl cerpegin; Ceropegia; Cerpegin; LC-MS; metabolite; Transcriptome

BQ-AurIPr: a redox-active anticancer Au(i) complex that induces immunogenic cell death - Mule, Ravindra D.; Kumar, Akhilesh; Sancheti, Shashank P.; Senthilkumar, B.; Kumar, Himanshu; Patil, Nitin T. (Chemical Science, 2022)
Immunogenic Cell Death (ICD) is a unique cell death mechanism that kills cancer cells while rejuvenating the anticancer immunosurveillance, thereby benefiting the clinical outcomes of various immuno-chemotherapeutic regimens. Herein, we report development of a library of benzo[a]quinolizinium-based Au(i) complexes through an intramolecular amino-auration reaction of pyridino-alkynes. We tested 40 candidates and successfully identified BQ-AurIPr as a novel redox-active Au(i) complex with potent anticancer properties. BQ-AurIPr efficiently triggered generation of DAMPs - the hallmarks of ICD - and was superior in terms of efficiency compared to FDA-approved drugs known to induce ICD. BQ-AurIPr significantly increased immunogenicity of cancer cells enhancing their phagocytosis when co-cultured with immune cells. Our investigation reveals that BQ-AurIPr induces oxidative stress inside mitochondria leading to mitophagy, as the mechanism for immunogenic cell death in A549 cells.

Interplay of anion-pi(+) and pi(+)-pi(+) interactions in novel pyrido[2,1-a]isoquinolinium-based aiegens - substituent- and counterion-dependent fluorescence modulation and applications in live cell mitochondrial imaging - Mule, Ravindra D.; Roy, Rupam; Mandal, Koushik; Chopra, Deepak; Dutta, Tanoy; Sancheti, Shashank P.; Shinde, Popat S.; Banerjee, Somsuvra; Lal Koner, Apurba; Bhowal, Rohit; Senthilkumar, Beeran; Patil, Nitin T. (Chemistry-A European Journal, 2022)
Recently, the concept of anion-pi(+) interactions has witnessed unique applications in the field of AIEgen development. In this contribution, we disclose a consolidated study of a library of N-doped ionic AIEgens accessed through silver-mediated cyclization of pyridino-alkynes. A thorough photophysical, computational and crystallographic study has been conducted to rationalize the observed substituent- and counterion-dependent fluorescence properties of these luminogens. We further elucidate the prominent role of anion-pi(+) interactions, pi(+)-pi(+) interactions and other non-covalent interactions, in inhibiting the undesired ACQ effect. Finally, we have also demonstrated the application of selected AIEgens for imaging of mitochondria in live cells.
Keywords: 1-a]isoquinolinium; AIEgens; anion-pi(+); crystal structure; mitochondrial imaging; pyrido[2